An integrative approach combining ion mobility mass spectrometry, X‐ray crystallography, and nuclear magnetic resonance spectroscopy to study the conformational dynamics of α1‐antitrypsin upon ligand binding. (14th July 2015) - Nyon, Mun Peak; Prentice, Tanya; Day, Jemma; Kirkpatrick, John; Sivalingam, Ganesh N.; Levy, Geraldine; Haq, Imran; Irving, James A.; Lomas, David A.; Christodoulou, John; Gooptu, Bibek; Thalassinos, Konstantinos
Abstract Native mass spectrometry (MS) methods permit the study of multiple protein species within solution equilibria, whereas ion mobility (IM)‐MS can report on conformational behavior of specific states. We used IM‐MS to study a conformationally labile protein (α1‐antitrypsin) that undergoes pathological polymerization in the context of point mutations. The folded, native state of the Z‐variant remains highly polymerogenic in physiological conditions despite only minor thermodynamic destabilization relative to the wild‐type variant. Various data implicate kinetic instability (conformational lability within a native state ensemble) as the basis of Z α1‐antitrypsin polymerogenicity. We show the ability of IM‐MS to track such disease‐relevant conformational behavior in detail by studying the effects of peptide binding on α1‐antitrypsin conformation and dynamics. IM‐MS is, therefore, an ideal platform for the screening of compounds that result in therapeutically beneficial kinetic stabilization of native α1‐antitrypsin. Our findings are confirmed with high‐resolution X‐ray crystallographic and nuclear magnetic resonance spectroscopic studies of the same event, which together dissect structural changes from dynamic effects caused by peptide binding at a residue‐specific level. IM‐MS methods, therefore, have great potential for further study of biologically relevant thermodynamic and kinetic instability of proteins and provide rapid and multidimensional characterization of ligand interactions of therapeutic interest.